¡Mandinga sea! : África en Antioquia : catálogo - Maya Restrepo, Luz Adriana; Cristancho, Raúl (Museo de Antioquia ; Ediciones Uniandes, 2015)
The exhibit "¡Mandinga Sea! Africa in Antioquia!" was initiated by the Museo de Antioquia as part of the events of the Bicentennial of Independence of the department of Antioquia (1813-2013), which took place between December 3, 2013 and March 3, 2014. This book, published in conjunction with the exhibition, invites readers to embark upon a voyage through time that begins from the coasts of West Africa and arrives at Antioquia, an artistic journey from the 16th century to today. Including 355 works of art of many different kinds, this exhibition seeks to make visible, to value, and to promote the creative, cultural, economic, social, political, technological, environmental, and historical legacies of the peoples of West Africa, and of their descendants who helped to build Antioquia. The goal of this book is to bring to the public, as well as to museum specialists and art historians, the discussion about the intersections that relate to the representation in museums of the Afro-American art and culture that was forged within the dynamics of both imperial and colonial slavery.